2017
DOI: 10.1080/07350015.2016.1149071
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Level Estimation of Optimal Consumption Choice With Intertemporal Nonseparability in Preferences and Measurement Errors

Abstract: This paper investigates the presence of habit formation in household consumption, using data from the Panel Study of Income Dynamics. We develop an econometric model of internal habit formation of the multiplicative specification. The restrictions of the model allow for classical measurement errors in consumption without parametric assumptions on the distribution of measurement errors. We estimate the parameters by nonlinear generalized method of moments and find that habit formation is an important determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…With this proposal, it was feasible to estimate both the evolution of the group decision-making process and the final solution before carrying out the group discussion process and consequently foreseeing possible actions. In 2018, Gayle and Khorunzhina [30] put forward an extended model based on fuzzy consensus while evaluating resources. By this model, rational decisions could be made so as to reduce the impact of individual preference on evaluation accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this proposal, it was feasible to estimate both the evolution of the group decision-making process and the final solution before carrying out the group discussion process and consequently foreseeing possible actions. In 2018, Gayle and Khorunzhina [30] put forward an extended model based on fuzzy consensus while evaluating resources. By this model, rational decisions could be made so as to reduce the impact of individual preference on evaluation accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the alternative route towards a separation of relative risk aversion and the EIS, which retains expected utility while ruling out intertemporal separability of preferences, this has been undertaken through the introduction of habit formation in the utility function. Habit-forming preferences have been employed in works aiming at the estimation of structural parameters such as Khvostova, Larin, and Novak (2016) and Gayle and Khorunzhina (2017). However, most studies relying on Euler equation estimation have found little or no evidence of habits, such as Meghir and Weber (1996) and Dynan (2000).…”
Section: Pignalosamentioning
confidence: 99%
“…For example, recent papers that use log-linearized Euler equations include Dogra and Gorbachev (2016), Huang et al (2015), Mazzocco (2007), and Mudit and Ravi (2016). On the other hand, recent papers that cite Carroll (2001) against the use of linearized Euler equation include Gomes and Issler (2017), Gayle and Khorunzhina (2016), Adams et al (2016), and Benito and Mumtaz (2009).…”
Section: Supplementary Materialsmentioning
confidence: 99%